PERAN KEPALA MADRASAH DAN MOTIVASI KERJA DALAM MEMPENGARUHI KINERJA GURU BERBASIS TEKNOLOGI DIGITAL - Saputra, Yusuf; Iskandar, Iskandar; Agung, Iskandar (Universitas Indraprasta PGRI, 2024)
This study aims to examine the role of school principals and work motivation in influencing teacher performance based on digital technology. The case study is conducted at Dayah Terpadu Almuslimun Lhoksukon. The research was carried out in North Aceh Regency in July 2024. The sample consists of 118 respondents. The research model uses quantitative statistics with WarpPLS software version 8.0. The results indicate that the leadership style of the school principal affects teacher performance. Additionally, work motivation influences teacher performance. The coefficient of determination for the endogenous variable of leadership style has an impact of 53.9% on teacher performance, with the remaining 47.1% being influenced by other variables not covered in this study.